Hesperetin, a Citrus Flavonoid, Ameliorates Inflammatory Cytokine-Mediated Inhibition of Oligodendroglial Cell Morphological Differentiation - Satoshi Nishino; Yoko Fujiki; Takanari Sato; Yukino Kato; Remina Shirai; Hiroaki Oizumi; Masahiro Yamamoto; Katsuya Ohbuchi; Yuki Miyamoto; Kazushige Mizoguchi; Junji Yamauchi (Neurology International, 2022)
Oligodendrocytes (oligodendroglial cells) are glial cells that wrap neuronal axons with their differentiated plasma membranes called myelin membranes. In the pathogenesis of inflammatory cytokine-related oligodendroglial cell and myelin diseases such as multiple sclerosis (MS), typical inflammatory cytokines tumor necrosis factor α (TNFα) and interleukin-6 (IL-6) are thought to contribute to the degeneration and/or progression of the degeneration of oligodendroglial cells and, in turn, the degeneration of naked neuronal cells in the central nervous system (CNS) tissues. Despite the known involvement of these inflammatory cytokines in disease progression, it has remained unclear whether and how TNFα or IL-6 affects the oligodendroglial cells themselves or indirectly. Here we show that TNFα or IL-6 directly inhibits morphological differentiation in FBD-102b cells, which are differentiation models of oligodendroglial cells. Their phenotype changes were supported by the decreased expression levels of oligodendroglial cell differentiation and myelin marker proteins. In addition, TNFα or IL-6 decreased phosphorylation levels of Akt kinase, whose upregulation has been associated with promoting oligodendroglial cell differentiation. Hesperetin, a flavonoid mainly contained in citrus fruit, is known to have neuroprotective effects. Hesperetin might also be able to resolve pre-illness conditions, including the irregulated secretion of cytokines, through diet. Notably, the addition of hesperetin into cells recovered TNFα- or IL-6-induced inhibition of differentiation, as supported by increased levels of marker protein expression and phosphorylation of Akt kinase. These results suggest that TNFα or IL-6 itself contributes to the inhibitory effects on the morphological differentiation of oligodendroglial cells, possibly providing information not only on their underlying pathological effects but also on flavonoids with potential therapeutic effects at the molecular and cellular levels.